Forecasting of the dynamics of aircraft components technical conductions in operation - Цуриков, О. Н. (Proceedings of National Aviation University (archive), 2000)
Considered is the problem of creation of simulation model of forecasting of the dynamics of aircraft components technical condition in the process of operation. Adoptation of the model to the elements, the technical condition of which is estimated by means of several controlled parameters is carried out